Tinjauan Hukum Ekonomi Islam Terhadap Pelacakan Status Industri Produk Halal - Masriani, Yulies Tiena; Mungawanah, Novia; Pakina, Ridho; Wahyuni, Husnia Hilmi (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2025)
The halal industry has grown rapidly, with approximately 1.8 billion global consumers and an annual transaction value reaching USD 650 million. Demand for halal products is increasing, making halal certification, halal standards, and halal traceability systems key factors in ensuring the halal status of food products. Indonesia, with an 87.2% Muslim population, has a large halal market and the potential to become a global halal economic hub. In this context, a halal traceability system is a crucial element in ensuring the integrity of halal products throughout the supply chain, from raw materials to consumers. Accurate information technology and documentation are key enablers in implementing this system. This study aims to examine the dynamics of the implementation of a halal traceability system and evaluate its role in halal product assurance in Indonesia, taking into account the contribution of Islamic economic law. The study also explores the challenges in implementing this system and how it can support the growth of the halal industry. Using a normative and analytical legal approach, this study hopes to provide policy recommendations to strengthen the halal assurance system, in accordance with Sharia principles, and support Indonesia as a major player in the global halal industry.